DISCRETE VARIABLE OPTIMUM DESIGN FOR THE PRESSURE VESSEL BASED ON IMPROVED FIREFLY ALGORITHM - CHEN DingLiang; ZHUO HongMing; CHEN QianQing (Jixie qiangdu)
In order to optimize the design of the pressure vessel,an optimization mathematical model was established. It takes the minimum quality of the pressure vessel shell as its optimization object,the inner diameter and wall thickness as its discrete design variables. The essay puts forward an improved firefly algorithm and it can improve the overall searching ability and the convergence performance of the algorithm by adopting the self-adaptive step size strategy,ignoring the local optimal strategy and the spatial domain constraint strategy. Simulation results show that compared with the normal one,improved firefly algorithm can converge to the optimal solution faster,and it can also effectively solve the problem of optimal design for the pressure vessel.